Temperature and energy effects on secondary electron emission from SiC ceramics induced by Xe17+ ions - Lixia Zeng (Nature Portfolio, 2017)
Abstract Secondary electron emission yield from the surface of SiC ceramics induced by Xe17+ ions has been measured as a function of target temperature and incident energy. In the temperature range of 463–659 K, the total yield gradually decreases with increasing target temperature. The decrease is about 57% for 3.2 MeV Xe17+ impact, and about 62% for 4.0 MeV Xe17+ impact, which is much larger than the decrease observed previously for ion impact at low charged states. The yield dependence on the temperature is discussed in terms of work function, because both kinetic electron emission and potential electron emission are influenced by work function. In addition, our experimental data show that the total electron yield gradually increases with the kinetic energy of projectile, when the target is at a constant temperature higher than room temperature. This result can be explained by electronic stopping power which plays an important role in kinetic electron emission.